Perancangan Sistem Informasi Absensi Magang Berbasis Website Menggunakan Framework CodeIgniter 3 di DISPERINDAG ESDM Garut - Imron Gozali (INTERNAL (Information System Journal), 2026)
Internship attendance is one of the most important aspects of the administrative process in government agencies. The manual attendance recording process often causes various problems, such as recording errors and delays in data recapitulation. This study aims to design and build a website-based internship attendance information system at the Garut Regency Department of Industry, Trade, Energy, and Mineral Resources (DISPERINDAG ESDM). The system was developed using the CodeIgniter 3 framework with a Model-View-Controller (MVC) architecture and a MySQL database. Data collection methods were carried out through observation, interviews, and documentation, while the system development method used the Prototype method that involved users in the process of evaluating and refining the system. The implementation results showed that the website-based internship attendance system was able to accelerate the attendance recording process, reduce data input errors, and produce more accurate and user-friendly information. Thus, the system developed can improve the effectiveness and efficiency of internship administration management in government agencies.